Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Arbuscular mycorrhizal fungi associated with Leptospermum scoparium (mānuka): effects on plant growth and essential oil content - Wisnu Adi Wicaksono; Catherine E. Sansom; E. Eirian Jones; Nigel B. Perry; Jana Monk; Hayley J. Ridgway (Symbiosis, 2018)

Biologically active compounds from Ozothamnus leptophyllus - Jacqueline E. Wood; Murray H. G. Munro; John W. Blunt; Nigel B. Perry; John R.L. Walker; Josephine M. Ward (New Zealand Journal of Botany, 1999)
A crude extract from a New Zealand native plant, Ozothamnus leptophyllus , was shown to possess antifungal activity. Flavonoids, mainly chalcones in the leaf exudate, were isolated, some of which possessed antiviral as well as antifungal activity. These flavanoids are excreted by glandular trichomes and form quasi‐crystalline deposits on the abaxial side of the leaves. 2’,4’,6'‐Trihydroxy‐chalcone was found to be active against both Polio virus (Pfizer vaccine strain) and Herpes simplex type 1 (ATCC VR 733); it was also responsible for anti‐dermatophytic activity against Trichophyton mentagrophytes . 2’,4'‐Dihydroxy‐4'‐methoxy‐dihydrochalcone was also active against both viruses.